2012
DOI: 10.1590/s1415-43662012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Fertigação do algodoeiro utilizando efluente doméstico tratado

Abstract: Conduziu-se um experimento no Campus da Universidade Federal Rural do Semiárido em Mossoró, RN, com o objetivo de avaliar o comportamento do algodoeiro (Gossypium hirsutum L. raça latifolium Hatch) cultivar 8H, quanto ao aspecto crescimento, quando irrigado com efluentes domésticos tratados. O delineamento experimental adotado foi o de blocos casualizados com parcelas subdivididas e sendo testadas, nas parcelas, as diluições do efluente doméstico [25% - T1, 50% - T2, 75% - T3 e 100% de água residuária- T4 e ág… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…This result indicates that only irrigation with 100% ETC caused an accumulation of nutrients with no need for mineral supplementation under the studied conditions. Similar results have also been found by [17] and [15], who observed that irrigation with wastewaters can replace mineral fertilization, because they provide sufficient amounts of nutrients for plants.…”
Section: Accumulation Of Dry Masssupporting
confidence: 87%
See 2 more Smart Citations
“…This result indicates that only irrigation with 100% ETC caused an accumulation of nutrients with no need for mineral supplementation under the studied conditions. Similar results have also been found by [17] and [15], who observed that irrigation with wastewaters can replace mineral fertilization, because they provide sufficient amounts of nutrients for plants.…”
Section: Accumulation Of Dry Masssupporting
confidence: 87%
“…The increase in SDM caused by the factor irrigation depth (L) may result from the accumulation of nutrients present in the treated domestic wastewater such as N, P and K (mean concentrations of 126.0, 13.7 and 43.6 mg L -1 , respectively) and of photoassimilates during photosynthesis [17,19]. As observed, greater water availability increases stomatal opening, favoring the entry of CO2 in the mesophyll, thus enhancing photosynthesis [18].…”
Section: Accumulation Of Dry Massmentioning
confidence: 99%
See 1 more Smart Citation
“…For the number of pods per plant, the renewable system with no fertiliser (S2A0) proved to be the same as the conventional system with mineral fertiliser (S1A1), which suggests that the nutritional contribution of the wastewater can completely replace mineral fertiliser in the cowpea crop. Sousa Neto et al [38] found that treated domestic effluent completely replaced mineral fertiliser when growing cotton. Freitas et al [13], growing cowpea (Vigna unguiculata (L.) Walp.)…”
Section: Source Of Variationmentioning
confidence: 99%
“…So much so, that it has increasingly being used in irrigated cultivations. Studies have already shown that the use of treated effluents in agriculture can increase agricultural productivity up to 60%, because of its considerable N (both organic and mineral), Ca, Mg and P contents (Almeida et al, 2012;Ludwig et al, 2012;Sousa Neto et al, 2012;Blum et al, 2013).…”
Section: Introductionmentioning
confidence: 99%